MindRegulation-SEL: Randomized controlled trial of the effects of a relaxation and guided imagery intervention with socioemotional learning on the psychological and biophysiological well-being, socioemotional development, cognitive function and academic achievement of elementary school children - Galinha, I. C.; Carvalho, J. L. da C. S. de.; Oliveira, A. C. P. de.; Arriaga, P.; Gaspar, A. D.; Silva, H. P.; Ortega, V. (Trials, 2025)
Background Mental imagery has long been used in psychological therapies, but only recently did research begin to provide a scientific background for it. Imagery interventions are inexpensive and a substantial body of research supports their effectiveness on anxiety reduction, behavior change, promotion of health outcomes, and adherence to medical interventions, in both adults and children. However, literature on the benefits of relaxation and guided imagery interventions for children in elementary school context is very scarce. This randomized controlled trial (RCT) aims to contribute to that knowledge by implementing and testing the benefits of an intervention program MindRegulation-Socioemotional Learning (MR-SEL) comprising breathing and progressive muscle relaxation, instructions for body posture, and guided imagery with socioemotional learning, conveying adaptive beliefs about oneself, the relationships with others and the environment. Method The MR-SEL intervention will be developed in the classroom for 15 min before learning activities, three times per week, for 5 months, and its effects will be measured on a range of psychosocial and emotional, biophysiological, and cognitive outcomes. Seventeen classes will be randomly assigned to three conditions: (a) relaxation and guided imagery with SEL (MR-SEL); (b) relaxation only; and (c) waitlist control. The RCT includes four data collection times: pretest, intermediate, posttest, and a 6-month follow-up. The sample comprises 259 students, elementary school third and fourth graders, 8–11 years old. The variables measured are well-being, affect, anxiety, emotional regulation, socioemotional competencies, attention and processing speed, and perceived benefits of the intervention. Physiological indicators of emotional arousal, emotional regulation, stress, and well-being are also taken, specifically, heart rate variability, electrodermal activity, actigraphy, and salivary DHEA-S and cortisol. The validity of the measures will be tested for the population and objectives of the study. Discussion Significant improvements on the children’s well-being, socioemotional regulation, cognitive function, physiological activity, and academic performance are expected after 5 months’ intervention at posttest and 11 months’ follow-up at MR-SEL condition, compared to the relaxation and control conditions. Changes in physiological activity are expected during MR-SEL and relaxation sessions. Emotional regulation, well-being, and anxiety are expected to mediate the effects of the interventions over socioemotional competence, cognitive function, and academic performance. Well-being and anxiety levels at pretest are expected to moderate the interventions’ effects.